2021
DOI: 10.48550/arxiv.2102.07725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Network Compression for Noisy Storage Devices

Abstract: Compression and efficient storage of neural network (NN) parameters is critical for applications that run on resource-constrained devices. Although NN model compression has made significant progress, there has been considerably less investigation in the actual physical storage of NN parameters. Conventionally, model compression and physical storage are decoupled, as digital storage media with error correcting codes (ECCs) provide robust error-free storage. This decoupled approach is inefficient, as it forces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Neural Network Compression. The interest in neural network compression research has increased sharply in the last decade [11,13,15,26] as the growing size of neural networks becomes a significant bottleneck in their deployment on resource-constraint devices [6,20]. Pruning is one of the neural network compression techniques that has been improved to the extent that today it is possible to prune more than 90% of the parameters of a trained model without a performance degradation [9,11,12,16].…”
Section: Related Workmentioning
confidence: 99%
“…Neural Network Compression. The interest in neural network compression research has increased sharply in the last decade [11,13,15,26] as the growing size of neural networks becomes a significant bottleneck in their deployment on resource-constraint devices [6,20]. Pruning is one of the neural network compression techniques that has been improved to the extent that today it is possible to prune more than 90% of the parameters of a trained model without a performance degradation [9,11,12,16].…”
Section: Related Workmentioning
confidence: 99%
“…Also fortunately, it is likely that 32 bits per floating point parameter is an order of magnitude more than necessary. Prior work has shown that simple model compression can be performed at 8 bits per floating point parameter [10,77,86] or even more aggressively at 1-4 bits per floating point parameter [30,34,35,54,75,85,87] with very low loss in performance, even with coordinate based networks such as NeRF [13,33]. However, since model compression is outside the scope of our work, we simply parameterize our results by the number of bits per floating point parameter.…”
Section: Side Informationmentioning
confidence: 99%
“…Substituting (11) into (10) suggests that minimizing MSE p is equivalent to minimizing MSE w with a modified prior Gaussian with mean µ λ and variance σ 2 λ (as opposed to µ p and σ 2 p ). Following (8), the estimate W that minimizes MSE p is then…”
Section: Bayesian Estimation With Compensatorsmentioning
confidence: 99%
“…These parameters are few in number. In practice, we can transmit/store them in a reliable manner (for example, via digital communication/storage [6] or protect them by repetition coding [11]).…”
Section: A Implementation Detailsmentioning
confidence: 99%
See 1 more Smart Citation